Exome sequencing‐based identification of mutations in non‐syndromic genes among individuals with apparently syndromic features. Issue 11 (26th August 2016) - Nishi, Eriko; Masuda, Koji; Arakawa, Michiko; Kawame, Hiroshi; Kosho, Tomoki; Kitahara, Masashi; Kubota, Noriko; Hidaka, Eiko; Katoh, Yuki; Shirahige, Katsuhiko; Izumi, Kosuke
Abstract : In a clinical setting, the number of organ systems involved is crucial for the differential diagnosis of congenital genetic disorders. When more than one organ system is involved, a syndromic diagnosis is suspected. In this report, we describe three patients with apparently syndromic features. Exome sequencing identified non‐syndromic gene mutations as a potential cause of part of their phenotype. The first patient (Patient 1) is a girl with cleft lip/palate, meningoencephalocele, tetralogy of Fallot, and developmental delay. The second and third patients (Patients 2 and 3) are brothers with developmental delay, deafness, and low bone mineral density. Exome sequencing revealed the presence of a CDH1 mutation in Patient 1 and a PLS3 mutation in Patients 2 and 3. CDH1 mutations are known to be associated with non‐syndromic cleft lip/palate, while PLS3 mutations are associated with osteoporosis. Thus, these variants may explain a part of the complex phenotype of the patients, although the effects of these missense variants need to be evaluated by functional assays in order to prove pathogenicity. On the basis of these findings, we emphasize the importance of scrutinizing non‐syndromic gene mutations even in individuals with apparently syndromic features. © 2016 Wiley Periodicals, Inc.